2002
DOI: 10.1097/01.asn.0000033277.32822.23
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Endothelial Fenestrae In Vivo Are Not Formed from Caveolae

Abstract: Abstract. Previous reports indicate that endothelial fenestrae in vitro can form by fusion of caveolae or caveolae-like vesicles. The principal aim of this study was to determine whether formation of glomerular endothelial cell fenestrae in vivo similarly involves caveolae and caveolin-1. Whereas caveolin-1 immunofluorescence was found around the circumference of human and mouse glomerular capillary loops, it co-localized only partially with the endothelium-specific lectin Ulex Europaeus I in human glomeruli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 29 publications
2
62
0
Order By: Relevance
“…[32][33][34] To understand the role of INF2 in maintaining nephrin-podocin complex trafficking, we investigated the interaction of INF2 with podocin and nephrin, as well as the lipid raft scaffolding protein caveolin-1. 35 As shown in Figure 4, A and B, in HEK 293T cells that overexpressed specific SD proteins, endogenous INF2 was co-immunoprecipitated with overexpressed hemagglutinin (HA)-podocin, but was immunoprecipitated by nephrin only in the presence of HA-podocin This finding indicates that podocin mediates an association of INF2 with nephrin. The interactions of endogenous INF2 with endogenous lipid raft components podocin and caveolin-1 were verified by co-immunoprecipitation in differentiated podocytes ( Figure 4C).…”
Section: Inf2 Directs Lipid Raft-mediated Lamellipodial Trafficking Omentioning
confidence: 84%
“…[32][33][34] To understand the role of INF2 in maintaining nephrin-podocin complex trafficking, we investigated the interaction of INF2 with podocin and nephrin, as well as the lipid raft scaffolding protein caveolin-1. 35 As shown in Figure 4, A and B, in HEK 293T cells that overexpressed specific SD proteins, endogenous INF2 was co-immunoprecipitated with overexpressed hemagglutinin (HA)-podocin, but was immunoprecipitated by nephrin only in the presence of HA-podocin This finding indicates that podocin mediates an association of INF2 with nephrin. The interactions of endogenous INF2 with endogenous lipid raft components podocin and caveolin-1 were verified by co-immunoprecipitation in differentiated podocytes ( Figure 4C).…”
Section: Inf2 Directs Lipid Raft-mediated Lamellipodial Trafficking Omentioning
confidence: 84%
“…It has also been suggested that VEGF-R1-Fyn/Yes complexes localize to caveolae fractions of endothelial cells (21), which might also be the case in podocytes. Of interest, caveolin-1, the principal protein that identifies caveolae in endothelial cells, is located in the foot processes of podocytes (39) and is therefore colocalized with nephrin. VEGF phosphorylation of its receptor in podocytes could induce the phosphorylation of the Src family of protein kinases, e.g., Fyn, and subsequently induce the phosphorylation of nephrin.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is also known to stimulate Fyn activa-tion in endothelial cells (29). Furthermore, VEGF receptors are known to colocalize with caveolin-1 in the plasma membrane of endothelial and mesangial cells (41), and caveolin-1 is coimmunoprecipitated with nephrin and CD2AP in podocytes (39). However, an association of VEGF receptors and nephrin has not been demonstrated.…”
mentioning
confidence: 99%
“…Because the ultrastructural lesions that occurred with albuminuria development in STZ-eNOS 2/2 mice occurred in podocytes, yet these cells are not known to express eNOS, 26 we hypothesized that the podocytopathy observed was a consequence of altered RAAS-dependent secreted factors. To determine whether podocyte morphology could be directly affected by circulating factors released in the setting of diabetes and eNOS deficiency, cultured podocytes were exposed to serum from the various study groups.…”
Section: Secreted Factors From Stz-enosmentioning
confidence: 99%